A mendelian randomization study investigates the causal relationship between immune cell phenotypes and cerebral aneurysm - Shi, Xingjie; Wang, Tao; Teng, Da; Hou, Shiqiang; Lin, Ning (Frontiers in Genetics, 2024)
Cerebral aneurysms (CAs) are a significant cerebrovascular ailment with a multifaceted etiology influenced by various factors including heredity and environment. This study aimed to explore the possible link between different types of immune cells and the occurrence of CAs.We analyzed the connection between 731 immune cell signatures and the risk of CAs by using publicly available genetic data. The analysis included four immune features, specifically median brightness levels (MBL), proportionate cell (PC), definite cell (DC), and morphological attributes (MA). Mendelian randomization (MR) analysis was conducted using the instrumental variables (IVs) derived from the genetic variation linked to CAs.After multiple test adjustment based on the FDR method, the inverse variance weighted (IVW) method revealed that 3 immune cell phenotypes were linked to the risk of CAs. These included CD45 on HLA DR+NK (odds ratio (OR), 1.116; 95% confidence interval (CI), 1.001−1.244; P = 0.0489), CX3CR1 on CD14-CD16-(OR, 0.973; 95% CI, 0.948 -0.999; P = 0.0447). An immune cell phenotype CD16-CD56 on NK was found to have a significant association with the risk of CAs in reverse MR Studies (OR, 0.950; 95% CI, 0.911 − 0.990; P = 0.0156).Our investigation has yielded findings that support a substantial genetic link between immune cells and CAs, thereby suggesting possible implications for future clinical interventions.